Effect of immobilization on styrene-divinylbenzene hydrophobic support on lipase properties - Sousa dos Santos, José Cleiton; Rueda, Nazzoly; Barbosa, Oveimar; García-Galán, Cristina; Hernández Sánchez, Karel; Rodrigues, Rafael C.; Fernández-Lafuente, Roberto (2014)
Trabajo presentado en el VII Workshop on Biocatalysis and Biotransformations - 1º Simposio Latinoamericano de Biocatalisis y Biotransformaciones, celebrado en Búzios (Brasil) del 23 al 26 de septiembre de 2014. [Introduction]: The immobilization of lipases on hydrophobic supports has been reported as a very efficient way to immobilize, purify and hyperactivate the lipases, allowing to keep the open form of the enzyme without any external interface. This communication shows the comparison between a very hydrophobic styrene-divinylbenzene matrix, MCI GEL CHP20P2,3, and octyl-Sepharose beads as supports to immobilize: lipases from Candida antarctica (B) Thermomyces lanuginosus (TLL) and Rhizomucor miehie (RML) and Lecitase Ultra, a commercial artificial phospholipase. The immobilization mechanism on both supports was similar: interfacial activation of the enzymes versus the hydrophobic surface of the supports. [Results and discussion]: Immobilization rate and loading capacity is much higher using MCI GEL CHP20P compared to octyl-Sepharose (e.g., 310 mg/g using RML). The thermal stability of all new preparations is much lower than that of the octyl-Sepharose immobilized lipases, while the opposite occurs in the presence of organic co-solvents. Regarding the hydrolytic activities, the results were strongly dependent on the substrate. Octyl-Sepharose immobilized enzymes were more active versus p-, while RML became 700- fold less active versus methyl phenylacetate. Thus, the immobilization of a lipase on this matrix needs to be empirically evaluated, since it may present very positive effects in some cases while in other cases it may have very negative ones. When used in esterification reactions in anhydrous media, the new biocatalysts offered advantages as higher reaction rate, more linear reaction courses and the possibility of use higher acid concentration. [Conclusion]: Thus, the immobilization of an enzyme on this matrix needs to be empirically evaluated, as in some cases may present very positive effects ...